2015
DOI: 10.1155/2015/157201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucagon-Like Peptide-1 Receptor Agonists on Weight Loss in Patients with Type 2 Diabetes: A Systematic Review and Network Meta-Analysis

Abstract: To evaluate the effectiveness of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) on weight reduction in patients with Type 2 diabetes mellitus (Type 2 DM), a network meta-analysis was conducted. MEDLINE, EMBASE, Cochrane Library, and ClinicalTrials.gov were searched from 1950 to October 2013. Randomized controlled trials (RCTs) involving GLP-1 RAs were included if they provided information on body weight. A total of 51 RCTs were included and 17521 participants were enrolled. The mean duration of 51 RCTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 36 publications
2
58
0
1
Order By: Relevance
“…GLP-1 also acts systemically on the pancreas, liver, heart, stomach and brain, impacting on gastric emptying, satiety and lipid absorption and metabolism 200 201. As such, a plethora of drugs have been developed as GLP-1R agonists or blockers (gliptins) of DPP-4, the enzyme that cleaves active GLP-1 in circulation 202. Although GLP-1-based therapies have been entirely targeted towards the treatment of T2D, it has become clear that this full-length form of the peptide may have significant potential as a T1D therapy.…”
Section: Probiotics As Diabetic Therapiesmentioning
confidence: 99%
“…GLP-1 also acts systemically on the pancreas, liver, heart, stomach and brain, impacting on gastric emptying, satiety and lipid absorption and metabolism 200 201. As such, a plethora of drugs have been developed as GLP-1R agonists or blockers (gliptins) of DPP-4, the enzyme that cleaves active GLP-1 in circulation 202. Although GLP-1-based therapies have been entirely targeted towards the treatment of T2D, it has become clear that this full-length form of the peptide may have significant potential as a T1D therapy.…”
Section: Probiotics As Diabetic Therapiesmentioning
confidence: 99%
“…While DPP-4Is are weight-neutral, GLP-1RAs (short-acting and long-acting) induce weight loss in a dose-dependent manner 59. Recently, a high-dose preparation of the long-acting GLP-1RA liraglutide (3.0 mg) has been approved for weight reduction 60.…”
Section: Gi Effects Of Glp-1 Based Therapiesmentioning
confidence: 99%
“…2 Their effects on glucose control are well established, [3][4][5] with additional benefits of weight loss, antihypertensive effects, and minimal risk of hypoglycemia. [4][5][6][7][8][9][10][11] A recent large randomised trial (SAVOR-TIMI 53 study 12 ) including patients with type 2 diabetes with established, or at risk for, cardiovascular disease, however, suggested possible increased mortality with saxagliptin versus placebo (5.1% v 4.6%). In response, the US Food and Drug Administration released the following statement in 2015: "A potential increase in all cause mortality with saxagliptin was observed-The ITT on-study analysis suggested an increase in all-cause mortality (HR=1.11, 95.1% CI [0.96 to 1.27]) based on about 800 observed deaths-Sensitivity analyses that censored subjects after treatment exposure showed more unfavorable trends in the risk of all cause mortality-Such trends were observed for both CV and non-CV related causes of death."…”
Section: Introductionmentioning
confidence: 99%